The Complexities of Mathilda’s Character as a Tragic Heroine in Mathilda by Mary Shelley - Arisya, Arisya; Jatmiko, Rahmawan (Universitas Gadjah Mada, 2024)
This research explores the character complexities of Mathilda as a tragic heroine, the main character in Mary Shelley's Mathilda, from the beginning until the end of the story. To achieve the aim of this research, the researchers use data collection and the novella Mathilda to analyze Mathilda's character. The approach for this research is psychoanalytic, theory of character and characterization, personality, and psychological process. The analysis shows that Mathilda is a complex tragic heroine who yearns for both affection and tragic death. Her experiences of unrequited parental affection and emotional turmoil contribute to her portrayal as a tragic character. However, her longing for her idealized tragic fate remains unfulfilled, adding complexity to her character. Despite her desires, she cannot obtain the tragic ending she seeks, further highlighting the tragic irony of her situation. Mathilda's portrayal as a tragic character highlights the depths of her desires and yearning and the complexities of her character.